2018
DOI: 10.26633/rpsp.2018.152
|View full text |Cite
|
Sign up to set email alerts
|

Developing nurse leaders across the Americas: evaluation of an online nursing leadership course

Abstract: Development of leadership capacities in the nursing workforce is essential to achieving universal health in the Region of the Americas. This evaluation considered the effectiveness of an online leadership course offered in English and Spanish to nurses throughout Latin America and the Caribbean. The online course was an asynchronous eight-module leadership nursing course created and offered by the Pan American Health Organization (PAHO) Virtual Campus. A retrospective, descriptive design was used to evaluate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…Within nursing organisations that are staffed by younger, more inexperienced nurses in positions of leadership, this could be an extremely challenging prospect as there could be serious implications for the organisation's productivity level. In an environment like the Caribbean where there continues to be brain drain of experienced professionals due to push/pull factors, this is particularly worrying from a leadership replacement perspective (Ortega et al, 2018;Salmon et al, 2007). Pfrimmer, Elenbaas, Melanson-Arnold, Harris, and…”
Section: Succession Planningmentioning
confidence: 99%
See 3 more Smart Citations
“…Within nursing organisations that are staffed by younger, more inexperienced nurses in positions of leadership, this could be an extremely challenging prospect as there could be serious implications for the organisation's productivity level. In an environment like the Caribbean where there continues to be brain drain of experienced professionals due to push/pull factors, this is particularly worrying from a leadership replacement perspective (Ortega et al, 2018;Salmon et al, 2007). Pfrimmer, Elenbaas, Melanson-Arnold, Harris, and…”
Section: Succession Planningmentioning
confidence: 99%
“…The recently published Global Advisory Panel on the Future of Nursing and Midwifery (GAPFON) report indicated that a common theme among participants in every region where consultations were conducted was the concern about the quality of leadership within nursing (Sigma Theta Tau International, 2017). During nursing training, priority is given to the development of core clinical skills with little emphasis on the development of leadership skills (Ortega et al, 2018).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Online education for leadership among practicing nurses is needed (Buckner et al, ; Dyess, Sherman, Pratt, & Chiang‐Hanisko, ). A study by Ortega et al of 289 nurses from 41 countries reported an online leadership programme was useful (Ortega et al, ) and all three cohorts improved in performance from pre‐test to post‐test. Of note, the programme included leadership as part of the components along with other aspects (e.g.…”
Section: Introductionmentioning
confidence: 99%